Network RTK 품질 분석 방법론별 성능 지표와 사용자 항법 정확도의 상관성 - 임철순; Cheol-soon Lim; 박병운; Byung-woon Park; 허문범; Moon-beom Heo (한국항행학회논문지, 2018)
정지한 객체의 측위에 사용되던 Network RTK (real time kinematics) 기술을 이동형 항체의 항법에 적용하기 위해서는 보정정보와 함께 사용자의 성능을 대표할 수 있는 지표가 함께 제공되어야 한다. 이를 위하여 본 논문에서는 I95 (ionospheric index 95) / G95(geodetic index 95), SBI (semivariance based index), RIU (residual interpolation uncertainty) 등의 지표 도출 알고리즘을 분석하고 이를 국토지리정보원의 기준국 원시 데이터와 VRS (virtual reference station) 사용자에 적용함으로써 정밀 항법 성능 지표로의 활용 가능성을 타진하였다. 24시간 데이터를 처리한 결과 보정정보의 비선형성을 나타낼 수 있는 RIU 지표와 Network RTK 사용자의 위치 정확도와의 상관성이 0.52로 타 지표에 비해 훨씬 높은 것으로 나타났으므로 향후 이동 항체의 항법 성능 지표로 사용이 가능할 것으로 예상된다. In order to apply the Network RTK (real time kinematics) technology, which has been used for positioning of stationary points, to the navigation of vehicles, its infrastructure should provide correction data with a quality indicator that can show the expected accuracy in real time. In this paper, we analyzed various indicator generation algorithms such as I95 (ionospheric index 95) / G95 (geodetic index 95), SBI (semivariance based index) and RIU (residual interpolation uncertainty). We also applied them to the raw observables from the reference stations of National Geographic Information Institute and VRS (virtual reference station) users, and then examined its feasibility to be used as a real-time performance index of the Network RTK rover. 24 hour data analysis shows that the RIU index, which can represent the non-linearty of the correction, has the strongest correlation with the Network RTK rover accuracy. Therefore, RIU index is expected to be used as a real-time performance index of the Network RTK rover.